(untitled) (ENTHYMEMA, 2020)
Introduction to the annual supplement “Volti del tradurre” by Helena Aguilà Ruzola and Donatella Siviero, containing a selection of articles based on some of the research presented at the VI Giornata internazionale sulla traduzione (Università di Palermo, 5-6 December 2019, in partnership with Universitat Autònoma de Barcelona and Università di Messina.